2023
DOI: 10.3390/arm91060041
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors Contributing to Reinfection by SARS-CoV-2: A Systematic Review

Walter Gómez-Gonzales,
Luis A. Chihuantito-Abal,
Carlos Gamarra-Bustillos
et al.

Abstract: This article aims to systematize the evidence regarding risk factors associated with COVID-19 reinfection. We conducted a systematic review of all the scientific publications available until August 2022. To ensure the inclusion of the most recent and relevant information, we searched the PubMed and Scopus databases. Thirty studies were reviewed, with a significant proportion being analytical observational case-control and cohort studies. Upon qualitative analysis of the available evidence, it appears that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 48 publications
1
0
0
Order By: Relevance
“…Additionally, factors such as fatigue from previous infections, differences in perceived susceptibility to reinfection, or variations in adherence to other preventive measures could also have influenced ATK usage behavior. These possibilities are aligned with Patel et al, 32 and Gómez-Gonzales et al 33 who stated that the likelihood of reinfection of COVID-19 depends on several factors, including infection treatment, immunopathogenesis, immune responses, rigorous adherence to appropriate behavior, and prevention strategies. Moreover, Mori et al 34 found that people with a history of COVID-19 were less likely to self-restraint from most social behaviors, and people whose acquaintance had been diagnosed with COVID-19 were significantly more likely to refrain from most social behaviors.…”
Section: Discussionsupporting
confidence: 58%
“…Additionally, factors such as fatigue from previous infections, differences in perceived susceptibility to reinfection, or variations in adherence to other preventive measures could also have influenced ATK usage behavior. These possibilities are aligned with Patel et al, 32 and Gómez-Gonzales et al 33 who stated that the likelihood of reinfection of COVID-19 depends on several factors, including infection treatment, immunopathogenesis, immune responses, rigorous adherence to appropriate behavior, and prevention strategies. Moreover, Mori et al 34 found that people with a history of COVID-19 were less likely to self-restraint from most social behaviors, and people whose acquaintance had been diagnosed with COVID-19 were significantly more likely to refrain from most social behaviors.…”
Section: Discussionsupporting
confidence: 58%